Catalytic Semi‐Water–Gas Shift Reaction: A Simple Green Path to Formic Acid Fuel. Issue 7 (17th March 2020) - Qadir, Muhammad I.; Castegnaro, Marcus V.; Selau, Felipe F.; Samperi, Mario; Fernandes, Jesum Alves; Morais, Jonder; Dupont, Jairton
Abstract: Formic acid (FA) is a promising CO and hydrogen energy carrier, and currently its generation is mainly centered on the hydrogenation of CO2 . However, it can also be obtained by the hydrothermal conversion of CO with H2 O at very high pressures (>100 bar) and temperatures (>200 °C), which requires days to complete. Herein, it is demonstrated that by using a nano‐Ru/Fe alloy embedded in an ionic liquid (IL)‐hybrid silica in the presence of the appropriate IL in water, CO can be catalytically converted into free FA (0.73 m ) under very mild reactions conditions (10 bar at 80 °C) with a turnover number of up to 1269. The catalyst was prepared by simple reduction/decomposition of Ru and Fe complexes in the IL, and it was then embedded into an IL‐hybrid silica {1‐ n ‐butyl‐3‐(3‐trimethoxysilylpropyl)‐imidazolium cations associated with hydrophilic (acetate, SILP‐OAc) and hydrophobic [bis((trifluoromethyl)sulfonyl)amide, SILP‐NTf2 ] anions}. The location of the alloy nanoparticles on the support is strongly related to the nature of the anion, that is, in the case of hydrophilic SILP‐OAc, RuFe nanoparticles are more exposed to the support surface than in the case of the hydrophobic SILP‐NTf2, as determined by Rutherford backscattering spectrometry. This catalytic membrane in the presence of H2 O/CO and an appropriate IL, namely, 1, 2‐dimethyl‐3‐ n ‐butylimidazolium 2‐methyl imidazolate (BMMIm⋅MeIm), is stable and recyclable for at least five runs, yielding a total of 4.34 m of free FA. Abstract : Green route to formic acid : A simple method for the production of formic acid by the simple catalytic carbonylation of water under very mild reaction conditions is demonstrated. The method employs supported bimetallic Ru/Fe nanoparticles in the presence of ionic liquids.